2015
DOI: 10.5511/plantbiotechnology.15.0408a
|View full text |Cite
|
Sign up to set email alerts
|

Screening RAPD primers to assess clonal fidelity in somatic embryos of Sawara cypress (<i>Chamaecyparis pisifera</i> Sieb. et Zucc.) and field performance of somatic embryo-derived trees

Abstract: In this study, 100 random amplified polymorphic DNA (RAPD) primers were screened to assess clonal fidelity in somatic embryos of Sawara cypress (Chamaecyparis pisifera Sieb. et Zucc.). Of the 100 primers tested, eight were selected based on their amplification products, which showed clear DNA fragmentation, generating 8.75 bands per primer in average. The amplification products showed no genetic variation among the tested somatic embryos. In addition, the performance of somatic embryo-derived trees was monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Although the SE-derived trees show a normal appearance, it is necessary to examine and monitor their genetic stability using molecular marker technologies. Genetic stability and good growth performance in the field are important criteria in the establishment of a practical protocol for SE (Hosoi et al, 2015).…”
Section: Growth In Vitro and Acclimatization Of Somatic Plantsmentioning
confidence: 99%
“…Although the SE-derived trees show a normal appearance, it is necessary to examine and monitor their genetic stability using molecular marker technologies. Genetic stability and good growth performance in the field are important criteria in the establishment of a practical protocol for SE (Hosoi et al, 2015).…”
Section: Growth In Vitro and Acclimatization Of Somatic Plantsmentioning
confidence: 99%
“…Six months after the plantlet conversion, the growth of 19 somatic lines was evaluated, making it-to the best of our knowledge-the first study to evaluate in vitro growth traits of SE-derived MSPs in sugi. In other conifers, growth traits of somatic plants have been evaluated for comparison with seedlings (seed-derived plants), and some of these studies reported lower growth performance of somatic plants compared with seedlings [21,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%